First record of the association of a species of Lycaenidae (Lepidoptera) with Zornia latifolia Sm. (Fabaceae), and its parasitoid (Hymenoptera: Chalcididae) in Brazil - Cajé, Suianne Oliveira dos Santos; Melo, Jefferson Duarte de; Silva, Erlande Lins da; Lima, Iracilda Maria de Moura (EntomoBrasilis, 2020)
The family Lycaenidae (Lepidoptera) comprises over 6,000 described and widely distributed species. However, studies on interactions with other insects such as ants, parasitoids, and with food plants in the Neotropical region, are still scarce, even though such information are fundamental for better understanding the natural history of this taxonomic group. This study reports a new food plant to larvae of Lycaenidae species in the neotropics, as well as its parasitoid. A Lycaenidae larva was found and collected for immature stage observation under laboratory conditions. The larva fed on petals and seeds of Zornia latifolia Sm. (Fabaceae). Nineteen days after pupation in laboratory a larvipupal parasitoid of the genus Conura (Chalcididae) had egressed. This is the first report of tritrophic relationship amongst Z. latifolia, a Lycaenidae larva and its larvipupal parasitoid of the genus Conura in a periurban area near remnants of the Atlantic Forest, in Northeastern Brazil.